Synthesis, Spectral and Biological Studies of Novel Schiff Base Metal Complexes Derived from Cephalexin and Sugars - Naz, Narjis; Sadiq, Zubi; Zafar Iqbal, Muhammad (Asian Journal of Chemistry, 2012)
Fe(II), Co(II) and Ni(II) metal complexes of novel Schiff bases derived from cephalexin and sugars (D-glucose, D-xylose) were synthesized and characterized by physio-chemical (elemental analysis, magnetic susceptibility and electrolytic conductance) and spectral techniques. It has been found that Schiff bases behave as bidentate ligands forming complexes with 1:2 (metal:ligand) stoichiometry. Thermal behaviour of complexes has been investigated using thermogravimetric techniques. The biological activities of complexes have been evaluated against two gram negative (Escherichia coli and Pseudomonas aeruginosa) and two gram positive (Bacillus subtilis and Staphylococcus aureus) bacteria by Agar diffusion disc method. It has been found that the complexes have higher activity as compared to the pure cephalexin against the bacteria.